Willingness to Pay for Electricity Access in Extreme Poverty : Evidence from Sub-Saharan Africa - Sievert, Maximiliane; Steinbuks, Jevgenijs (World Bank, Washington, DC, 2019)
Improving electricity access in low-income countries is a challenging problem because of the high costs of grid extension and low demand for grid electricity in rural areas. This study elucidates these constraints by analyzing poor households' willingness-to-pay for different types of electricity access, including lower cost off-grid technologies. The theoretical model illustrates how consumer preferences, operational and capital costs of electricity service delivery, and availability of power supply affect households' decisions to acquire electricity technology. These effects are then assessed empirically by estimating beneficiaries' willingness-to-pay for electricity in three low-income countries that have pockets of households living in extreme poverty -- Burkina Faso, Senegal, and Rwanda. Consistent with the theoretical model, the results indicate very low household willingness-to-pay for electricity access, and that willingness-to-pay diminishes as households' income declines. Therefore, the study recommends concentrating in the nearer term on ultra-low-cost decentralized off-grid solar technologies in programs to provide household electricity to the poor in rural areas.